In Consideration of the Needs of Caregivers: Grandparenting Experiences in Manitoba First Nation Communities - Eni, Rachel; Harvey, Carol D.H.; Phillips-Beck, Wanda (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2009)
Grandparents are valued in traditional and contemporary Aboriginal societies. In this paper we summarize traditional knowledge from Manitoba Aboriginal experiences, and we provide data from contemporary on-reserve grandmothers. Data for this study were collected in 2007 in 16 First nations Manitoba communities. Open-ended semi-structured in-person interviews were conducted in maternal-child centers that provide programs for developmental health for children and their parents (prenatal to age 6). Of the 100 people interviewed, ten of those were grandmothers, and their stories are analyzed in this paper. Results showed that grandmothers provided cultural transmission to subsequent generations, ensured child safety, provided acceptance and care for grandchildren, were challenged by inadequate and unsafe housing and communities, had difficulty proving educational supports for grandchildren, were supported by a network of kin, found community support inconsistent, needed to make a living, and needed more health supports. Implications for policy and research are given at the end of the paper.